Effect of multi-grip myoelectric prosthetic hands on daily activities, pain-related disability and prosthesis use compared with single-grip myoelectric prostheses: A single-case study - Cathrine Widehammar; Ayako Hiyoshi; Kajsa Lidström Holmqvist; Helen Lindner; Liselotte Hermansson (Medical Journals Sweden, 2022)
Objective: To evaluate the effect of multi-grip myoelectric prosthetic hands on performance of daily activities, pain-related disability and prosthesis use, in comparison with single-grip myoelectric prosthetic hands.  Design: Single-case AB design. Patients: Nine adults with upper-limb loss participated in the study. All had previous experience of single-grip myoelectric prostheses and were prescribed a prosthesis with multi-grip functions. Methods: To assess the changes in daily activities, pain-related disability and prosthesis use between single-grip and multi-grip myoelectric prosthetic hands, the Canadian Occupational Performance Measure, Pain Disability Index, and prosthesis wearing time were measured at multiple time-points. Visual assessment of graphs and multi-level linear regression were used to assess changes in the outcome measures.  Results: At 6 months' follow-up self-perceived performance and satisfaction scores had increased, prosthesis wearing time had increased, and pain-related disability had reduced in participants with musculoskeletal pain at baseline. On average, 8 of the 11 available grip types were used. Most useful were the power grip, tripod pinch and lateral pinch.  Conclusion: The multi-grip myoelectric prosthetic hand has favourable effects on performance of, and satisfaction with, individually chosen activities, prostheses use and pain-related disability. A durable single-grip myoelectric prosthetic hand may still be needed for heavier physical activities. With structured training, a standard 2-site electrode control system can be used to operate a multi-grip myoelectric prosthetic hand. Lay Abstract Individuals with upper limb loss are often offered prosthetic hands during the rehabilitation process, to restore body balance and compensate for lack of grip ability. Prosthetic hands with multiple grip functions have been developed to facilitate fine motor skills and enable an ergonomic movement pattern. However, the impact of these hands on the users' daily life has been sparsely studied, and the results have been inconsistent. This study evaluates the effect of multi-grip hands on the performance of daily activities, pain-related disability and prosthesis use, compared to single-grip hands. Based on our results, a multi-grip hand was more useful than a single-grip model for performance of specific, individually chosen activities. Further, prosthesis use increased and pain-related disability was reduced by the use of a multi-grip hand. Multi-grip prosthetic hands seem to fill a gap in prosthetic rehabilitation and facilitate activity performance, and are something clinicians can recommend to their patients.